What We Really Value Beyond Rubrics in Teaching and Assessing Writing - Broad, Bob (University Press of Colorado, 2003)
What We Really Value traces the origins of traditional rubrics within the theoretical and historical circumstances out of which they emerged, then holds rubrics up for critical scrutiny in the context of contemporary developments in the field. As an alternative to the generic character and decontextualized function of scoring guides, he offers dynamic criteria mapping, a form of qualitative inquiry by which writing programs (as well as individual instructors) can portray their rhetorical values with more ethical integrity and more pedagogical utility than rubrics allow. To illustrate the complex and indispensable insights this method can provide, Broad details findings from his study of eighty-nine distinct and substantial criteria for evaluation at work in the introductory composition program at "City University." These chapters are filled with the voices of composition instructors debating and reflecting on the nature, interplay, and relative importance of the many criteria by which they judged students' texts. Broad concludes his book with specific strategies that can help writing instructors and programs to discover, negotiate, map, and express a more robust truth about what they value in their students' rhetorical performances.